PENGARUH CASH TURNOVER, INVENTORY TURNOVER, DEBT TO EQUITY DAN WORKING CAPITAL TOTAL ASSET RATIO TERHADAP RETURN ON ASSET (ROA) PADA SAUDIA TOSERBA COMAL - Rizka Ariyanti Ariyanti; Jilma Dewi A; Muhammad Zain Zain (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
This study aims to determine the influence return on assets consists of cash turnover, inventory turnover, debt to equity and working capital to total assets ratio. This research was conducted on Arabia Comal Department Store in 2016-2018 with the object of research is the Shop Saudi Toserba in Comal uses the method of multiple linear regression analysis. Based on the results of the partial cash turnover test it has no effect significant, inventory turnover has a significant negative effect, debt to equity does not have a significant effect and working capital to total assets ratio has a significant effect on return on assets in stores Saudi Comal Department Store. Simultaneous cash turnover, inventory turnover, debt to equity and working capital to asset ratio significantly influence return on assets. The adjusted R square value is 49.10% which means that variable cash turnover, inventory turnover, and sales growth are able explained 49,10% of the causes of variations or changes which occurred on return on assets while the remaining 50.90% influenced by other variables not included in this study.